An antibacterial wound healing hydrogel based on carboxymethyl chitosan / carbon nitride / polyvinyl alcohol

By combining carboxymethyl chitosan and carbon nitride in the hydrogel, the problem that the prior art is difficult to effectively inhibit bacteria under visible light irradiation is solved, and a hydrogel with good antibacterial properties under visible light is achieved, which promotes wound healing.

CN119499440BActive Publication Date: 2025-04-25CHINA JILIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510082233.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively inhibit bacteria under visible light irradiation, limiting the efficiency of wound healing.

Method used

An antibacterial wound healing hydrogel based on carboxymethyl chitosan/carbon nitride/polyvinyl alcohol is used to form a hydrogel with good antibacterial properties through the synergistic effect of carboxymethyl chitosan and carbon nitride.

Benefits of technology

Under visible light, the hydrogel significantly improves the antibacterial effect and promotes the healing of bacterial infection wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499440B_ABST
    Figure CN119499440B_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial wound healing hydrogel based on carboxymethyl chitosan / carbon nitride / polyvinyl alcohol, which is prepared by using carboxymethyl chitosan, carbon nitride and polyvinyl alcohol as raw materials and boric acid as a cross-linking agent. The carbon nitride and carboxymethyl chitosan of the invention cooperate in antibacterial activity, so that the gel can exert good antibacterial performance under visible light, which is beneficial to the healing of wounds infected by bacteria.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel production, and in particular to an antibacterial wound healing-promoting hydrogel based on carboxymethyl chitosan / carbon nitride / polyvinyl alcohol. Background Art

[0002] Carboxymethyl chitosan is an important water-soluble chitosan derivative with many medical effects, such as promoting wound healing, hemostasis, inhibiting scars, analgesia and antibacterial effects. It is also widely used in chemical industry, environmental protection and health care products. Carboxymethyl chitosan has good biocompatibility and biodegradability. It is widely used in hydrogels and wound healing biomaterials, and is also widely used in tissue engineering matrix materials. In addition, carboxymethyl chitosan can be easily processed into nanoparticles, making it more suitable for drug delivery, bioimaging, biosensors and gene therapy. In recent years, carboxymethyl chitosan has also been widely used in green chemistry. Due to its unique biological properties, carboxymethyl chitosan has a wide range of applications in biomedicine and pharmaceutical fields.

[0003] Carbon nitride (C3N4) is a new type of material with a hardness comparable to that of diamond. It is an atomic crystal composed of carbon and nitrogen elements. Its chemical formula is C3N4. There are 4 nitrogen atoms around each carbon atom, and 3 carbon atoms around each nitrogen atom. Adjacent atoms are bonded by strong covalent bonds to form a spatial network structure.

[0004] Graphitic carbon nitride (g-C3N4) is a semiconductor photocatalyst with good visible light absorption, suitable band structure and non-metallic properties, and has received extensive attention in the field of photocatalysis. However, due to the violent exciton effect, severe carrier recombination process and large block structure, the initial photocatalytic activity of g-C3N4 is weak, which greatly limits its application in the field of photocatalysis. Under visible light irradiation, g-C3N4 can produce a certain amount of active oxides, which destroy the structure and function of bacterial cells, thereby causing their death. Summary of the invention

[0005] The purpose of the present invention is to provide an antibacterial wound healing hydrogel based on carboxymethyl chitosan / carbon nitride / polyvinyl alcohol. Carbon nitride and carboxymethyl chitosan have synergistic antibacterial properties, so that the gel can exert good antibacterial properties under visible light, which is beneficial to the healing of wounds infected with bacteria.

[0006] The technical solution adopted by the present invention to solve the technical problem is:

[0007] An antibacterial wound healing hydrogel based on carboxymethyl chitosan / carbon nitride / polyvinyl alcohol is prepared with carboxymethyl chitosan, carbon nitride, and polyvinyl alcohol as raw materials and boric acid as a cross-linking agent. The specific preparation method is as follows:

[0008] Dissolve carboxymethyl chitosan in deionized water and stir evenly, then disperse carbon nitride in the carboxymethyl chitosan aqueous solution and stir evenly to obtain a carboxymethyl chitosan / carbon nitride solution; then add a polyvinyl alcohol aqueous solution and mix evenly, then add a boric acid aqueous solution and stir to form a carboxymethyl chitosan / carbon nitride / polyvinyl alcohol hydrogel;

[0009] In the carboxymethyl chitosan / carbon nitride solution, the concentration of carboxymethyl chitosan is 0.04-0.06 g / mL, the concentration of carbon nitride is 2-3 g / L; the concentration of the polyvinyl alcohol aqueous solution is 0.1-0.15 g / mL; the concentration of the boric acid aqueous solution is 0.02-0.04 g / mL; the volume ratio of carboxymethyl chitosan / carbon nitride solution: polyvinyl alcohol aqueous solution: boric acid aqueous solution = 10-15:25-30:4-6.

[0010] Carboxymethyl chitosan itself has certain antibacterial and anti-inflammatory capabilities, which makes up for the deficiency of natural chitosan that can only be dissolved in acid, creates conditions for the formation of borate bonds, and also has a good promoting effect on wound healing. The inventor unexpectedly discovered in the study that carboxymethyl chitosan and carbon nitride combined to form a hydrogel have a significant synergistic antibacterial effect, which greatly improves the antibacterial effect of the two when used alone.

[0011] Preferably, the carbon nitride is graphite phase carbon nitride.

[0012] Preferably, the preparation method of the graphite phase carbon nitride is: taking urea as a precursor and placing it in a muffle furnace, heating it to 500°C at a heating rate of 20°C / min, calcining it at 500°C for 2h and then further heating it to 520°C and continuing to calcine for 2h, after cooling, grinding the product and collecting the yellow powder, which is g-C3N4.

[0013] The beneficial effects of the present invention are as follows: carbon nitride and carboxymethyl chitosan have synergistic antibacterial properties, so that the gel can exert good antibacterial properties under visible light, which is beneficial to the healing of wounds infected by bacteria. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is the infrared spectrum of the material of Example 4;

[0015] Figure 2 This is the full XPS spectrum of the material of Example 4;

[0016] Figure 3 is the XPS C1s spectrum of the material of Example 4;

[0017] Figure 4 is the XPS N1s spectrum of the material of Example 4;

[0018] Figure 5 This is a picture of the wound healing of mouse skin. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described in detail below through specific embodiments.

[0020] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, unless otherwise specified, are all conventional methods in the art.

[0021] Source of materials: Polyvinyl alcohol (PVA, alcoholysis degree: 98.0 ~ 99.0%, viscosity: 54.0 ~ 66.0 mPa.s), boric acid (H3BO3, AR, ≥99.5%) were purchased from Shanghai McLean Reagent Co., Ltd., China. Carboxymethyl chitosan (CMCS, carboxylation degree ≥80%) was purchased from Shanghai Yuanye Biotechnology Co., Ltd., China. Escherichia coli (ATCC 25922) and Staphylococcus aureus (ATCC25923) were from China General Microbiological Culture Collection Center.

[0022] Example 1: Preparation of graphite phase carbon nitride

[0023] Urea was used as a precursor and placed in a muffle furnace. The temperature was raised to 500°C at a heating rate of 20°C / min. After calcination at 500°C for 2 hours, the temperature was further raised to 520°C and calcination was continued for 2 hours. After cooling, the product was ground and the yellow powder was collected, which was g-C3N4.

[0024] Example 2: Preparation of CMCS / g-C3N4 / PVA hydrogel (all operations were performed at room temperature)

[0025] (1) Polyvinyl alcohol was dissolved in deionized water, and heated in a water bath at 95°C for 2 h under stirring to obtain a polyvinyl alcohol aqueous solution with a concentration of 0.1 g / mL;

[0026] (2) dissolving carboxymethyl chitosan in deionized water and stirring evenly, then dispersing the graphite phase carbon nitride prepared in Example 1 in the carboxymethyl chitosan aqueous solution and stirring evenly to obtain a carboxymethyl chitosan / carbon nitride solution, wherein the concentration of carboxymethyl chitosan is 0.04 g / mL and the concentration of carbon nitride is 2 g / L;

[0027] (3) Then, 30 mL of polyvinyl alcohol aqueous solution was added to 15 mL of carboxymethyl chitosan / carbon nitride solution and mixed evenly. Then, 6 mL of 0.02 g / mL boric acid aqueous solution was added and stirred to form a carboxymethyl chitosan / carbon nitride / polyvinyl alcohol hydrogel.

[0028] Example 3: Preparation of CMCS / g-C3N4 / PVA hydrogel (all operations were performed at room temperature)

[0029] (1) Polyvinyl alcohol was dissolved in deionized water, and heated in a water bath at 95°C for 2 h under stirring to obtain a polyvinyl alcohol aqueous solution with a concentration of 0.15 g / mL;

[0030] (2) dissolving carboxymethyl chitosan in deionized water and stirring evenly, then dispersing the graphite phase carbon nitride prepared in Example 1 in the carboxymethyl chitosan aqueous solution and stirring evenly to obtain a carboxymethyl chitosan / carbon nitride solution, wherein the concentration of carboxymethyl chitosan is 0.06 g / mL and the concentration of carbon nitride is 3 g / L;

[0031] (3) Then, 25 mL of polyvinyl alcohol aqueous solution was added to 10 mL of carboxymethyl chitosan / carbon nitride solution and mixed evenly. Then, 5 mL of 0.04 g / mL boric acid aqueous solution was added and stirred to form a carboxymethyl chitosan / carbon nitride / polyvinyl alcohol hydrogel.

[0032] Example 4: Preparation of CMCS / g-C3N4 / PVA hydrogel (all operations were performed at room temperature)

[0033] (1) Polyvinyl alcohol was dissolved in deionized water, and heated in a water bath at 95°C for 2 h under stirring to obtain a polyvinyl alcohol aqueous solution with a concentration of 0.1 g / mL;

[0034] (2) dissolving carboxymethyl chitosan in deionized water and stirring evenly, then dispersing the graphite phase carbon nitride prepared in Example 1 in the carboxymethyl chitosan aqueous solution and stirring evenly to obtain a carboxymethyl chitosan / carbon nitride solution, wherein the concentration of carboxymethyl chitosan is 0.05 g / mL and the concentration of carbon nitride is 2.45 g / L;

[0035] (3) Then, 25 mL of polyvinyl alcohol aqueous solution was added to 10 mL of carboxymethyl chitosan / carbon nitride solution and mixed evenly. Then, 4 mL of 0.03 g / mL boric acid aqueous solution was added and stirred to form carboxymethyl chitosan / carbon nitride / polyvinyl alcohol hydrogel (CMCS / g-C3N4 / PVA hydrogel, referred to as PCBg gel).

[0036] Comparative Example 1: Preparation of CMCS / PVA hydrogel

[0037] The difference between this example and Example 4 is that no g-C3N4 was added during the preparation process, and CMCS / PVA hydrogel, referred to as PCB gel, was obtained.

[0038] Comparative Example 2: Preparation of g-C3N4 / PVA hydrogel

[0039] The difference between this example and Example 4 is that CMCS was not added during the preparation process to obtain g-C3N4 / PVA hydrogel.

[0040] The material prepared in Example 4 was used as a representative for performance testing:

[0041] Material characterization

[0042] 1. Fourier infrared spectroscopy analysis

[0043] The structure of the freeze-dried hydrogel was studied by Fourier transform infrared spectroscopy (FTIR). The freeze-dried hydrogel sample was ground into powder, mixed with KBr and ground, and then pressed into a tablet press to form a sample. The sample was detected by FTIR spectrometer at 4000-500 cm -1 The FTIR spectrum in the range is used to obtain the changes in the chemical structure of the hydrogel:

[0044] like Figure 1 As shown in the spectrum of CMCS, 3410 cm -1 The strong and broad absorption peaks near 1610 cm are the stretching vibration absorption peaks of OH and NH. -1 and 1423 cm -1 The absorption peaks near are the asymmetric and symmetric stretching vibration peaks of -COOH, indicating the presence of carboxyl groups. In the PVA spectrum, the spectrum of the PVA sample is at 3440 cm -1 and 1423 cm -1 There are obvious absorption peaks at 810 cm. These peaks are OH stretching vibration peak, CH-OH bending vibration peak and CO stretching vibration peak. -1 and 1200~1600 cm -1 The characteristic peaks at 3400~3000 cm-1 correspond to the breathing vibration mode of the triazine ring and the stretching vibration mode of the CN heterocycle in the g-C3N4 framework. -1 The broad peaks in the range of 1610 cm-1 are attributed to the stretching vibration of NH. -1 and 1423 cm -1 There is an obvious characteristic absorption peak at 1420 cm -1 and 1330 cm -1 The tensile peak at 1200 ~ 1600 cm-1 in CMCS / g-C3N4 shows that the cross-linking is successful. -1 The characteristic absorption peak at . The results show that g-C3N4 exists in the hydrogel.

[0045] 2. XPS analysis

[0046] X-ray photoelectron spectroscopy (XPS) is used to characterize the occurrence state, chemical bonds and other information of the elements in the aerogel material. XPS is used to supplement the successful cross-linking of carbon nitride:

[0047] Figure 2 It shows that the gel is mainly composed of C, N, and O elements. Figure 3 In the high-resolution XPS spectrum of C1s, the C1s peaks are located at 284.80 and 288.40 eV, corresponding to the sp 2 C atoms and N=C=N species. The CN / CO and COC / C=O functional groups in the composite hydrogel structure showed peaks at 286.28 eV and 287.26 eV, respectively. Figure 4 The high-resolution XPS spectrum of N1s can be divided into three components: the main peak at 398.68 eV is the CN=C coordination, which comes from the sp 2 The bonded N indicates the presence of g-C3N4 in the hydrogel, while the other two weak peaks with higher binding energies (about 399.60 and 401.10 eV) belong to N-(C)3 and CNH, respectively.

[0048] In vitro antibacterial

[0049] Select Gram-negative Escherichia coli ( E. coli , ATCC 25922) and Gram-positive Staphylococcus aureus ( S. aureus , ATCC 25923) to carry out in vitro antibacterial experiments. The plate counting method was used to evaluate the antibacterial effect of the hydrogel. First, the prepared hydrogel was transferred to a sterile test tube, and 100 μL of fresh suspension of Staphylococcus aureus and Escherichia coli (1×10 4 CFU / mL). Incubate for 1 h under visible light irradiation (300 W xenon lamp, λ> 420 nm, with UV cutoff filter), add 1 mL PBS to a sterile test tube and elute. The bacteria treated with visible light irradiation were used as the control (Control group). 100 μL of the collected bacterial suspension was spread on tryptic soy agar (TSA) or Baird-Parker agar (BP) plates and counted after 18-20 h of incubation. The results are shown in Table 1. The bactericidal rate of Escherichia coli in Example 1 was 52.33%, the bactericidal rate of PCBg gel was 86.81%, and the bactericidal rate of Example 2 was 66.36%. The bactericidal rate of Staphylococcus aureus in Example 1 was 70.37%, the bactericidal rate of PCBg gel was 94.31%, and the bactericidal rate of Example 2 was 70.53%.

[0050] Table 1 Bactericidal effect

[0051]

[0052] The synergistic effect of bactericidal factors is determined by the T / E ratio, where T represents the theoretical survival rate, which is the product of the survival rates of each single factor; E represents the survival rate of microorganisms after the combined action; a TE ratio greater than 1 indicates a synergistic effect (see "Practical Tutorial on Hospital Disinfection" by Xu Shiai et al., page 30, Hebei Science and Technology Press, publication date: 20140630).

[0053] T / E( E. coli ) = (47.67%*33.64%) / 13.19%=1.22﹥1

[0054] T / E( S. aureus )=(29.63%*29.47%) / 5.69%=1.53﹥1.

[0055] Therefore, the hydrogel formed by the carbon nitride and carboxymethyl chitosan of the present invention has a synergistic antibacterial effect.

[0056] Hydrogel repairs skin damage in mice

[0057] Healthy male C57 mice were purchased from Shanghai Jiesijie Experimental Animal Co., Ltd. They were 10-12 weeks old and weighed 25-30g. They were kept in an SPF animal room. The experimental animals had free access to water and food and received a 12h / 12h cycle of light / darkness. Staphylococcus aureus (ATCC 25923) was inoculated on a nutrient agar slant and cultured at 35-37℃ for 24h before inoculating into TBS liquid culture medium (tryptone 17.0g, soytone 3g, sodium chloride 5g, potassium dihydrogen phosphate 2.5g, glucose 2.5g, distilled water to 1L), and continued to be cultured at 35-37℃ for 16h before aspirating the bacterial solution, centrifuging and removing the supernatant, and then preparing the model bacterial solution (10^6CFU / mL) with sterile saline. The mice were randomly divided into 3 groups (n=5): 1. Model group; 2. PCB group; 3. PCBg group. After adaptive feeding, mice in each group were anesthetized with 2.5% Avertin (150 μL / 10 g). The backs of the anesthetized mice were depilated, and a skin puncher was used to make holes with a diameter of 0.8 cm on the left and right sides of the spine. The depth of the holes was enough to damage the mouse cortex. After cleaning the wound site with a sterile cotton swab, 0.1 mL of Staphylococcus aureus liquid was dripped into each wound of the mouse. After waiting for half an hour after the dripping of the liquid, the intervention began: the PCB group and the PCBg group applied PCB hydrogel or PCBg hydrogel dressing according to the specified dose to ensure that it covered the entire wound and then bandaged it with a film. Both the PCB group and the PCBg group were exposed to xenon light for 10 minutes a day. Observation and photography were performed every 2 days. According to Figure 5The final healing rate was calculated from the wound healing status diagram. The healing rate of the PCBg gel group was as high as 98.13%; the healing rate of the PCB gel group was 89.46%. It is obvious that the present invention can significantly improve the healing rate.

[0058] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.

Claims

1. An antibacterial wound healing hydrogel based on carboxymethyl chitosan / carbon nitride / polyvinyl alcohol, characterized in that: It is prepared with carboxymethyl chitosan, carbon nitride, and polyvinyl alcohol as raw materials and boric acid as a cross-linking agent. The specific preparation method is as follows: Dissolve carboxymethyl chitosan in deionized water and stir evenly, then disperse carbon nitride in the carboxymethyl chitosan aqueous solution and stir evenly to obtain a carboxymethyl chitosan / carbon nitride solution; then add a polyvinyl alcohol aqueous solution and mix evenly, then add a boric acid aqueous solution and stir to form a carboxymethyl chitosan / carbon nitride / polyvinyl alcohol hydrogel; In the carboxymethyl chitosan / carbon nitride solution, the concentration of carboxymethyl chitosan is 0.04-0.06 g / mL, the concentration of carbon nitride is 2-3 g / L; the concentration of the polyvinyl alcohol aqueous solution is 0.1-0.15 g / mL; the concentration of the boric acid aqueous solution is 0.02-0.04 g / mL; the volume ratio of carboxymethyl chitosan / carbon nitride solution: polyvinyl alcohol aqueous solution: boric acid aqueous solution = 10-15:25-30:4-6; The carbon nitride is graphite phase carbon nitride.

2. The antibacterial wound healing-promoting hydrogel according to claim 1, characterized in that: The preparation method of the graphite phase carbon nitride is as follows: urea is used as a precursor and placed in a muffle furnace, the temperature is increased to 500°C at a heating rate of 20°C / min, after calcining at 500°C for 2h, the temperature is further increased to 520°C and calcined for 2h, after cooling, the product is ground and a yellow powder is collected, namely g-C3N4.